Sejarah Uang Dirham Kesultanan Samudera Pasai: Kontribusi terhadap Peradaban Islam di Indonesia - Shihabuddin, Ahmad; Roza, Ellya (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2023)
Samudera Pasai dirham money is the oldest currency in the archipelago which has many versions and changes but at this time it is considered an antique that is made history. The research method used by the author is using the library research method which means research activities carried out by collecting information that is used as a reference from books or articles of previous researchers by reviewing and quotingThe results of the author's research using the library research method are the history of the emergence of dirham money during the Samudera Pasai Sultanate in the 13th century by Sultan Malikulsaleh with gold content on the dirham money.